Mouse models of the nuclear envelopathies and related diseases - Stewart, Colin L. (Current topics in developmental biology, 2014)
Volume 109 of Current Topics in Developmental Biology covers mouse models of the nuclear envelopathies and related diseases, with contributions from an international board of authors. The chapters provide a comprehensive set of reviews covering such topics as mouse models neurodegenerative diseases including Parkinson's and dystonia, muscle ageing and sarcopenia, cardiac failure and repair, ageing and prospects lifespan extension, lipodystrophy and the significance in fat regulation, also identifying developmental mutations in mammals and nuclear envelope and LINC complex in disease.<br.